Works Like a Charm Incentive Rhetoric and the Economization of Everyday Life - McDonald, Robert O. (State University of New York Press, 2023)
Breaks the spell of economic thought by interrogating the widespread language and logic of "incentives" in public life from a Lacanian perspective
Description based on publisher supplied metadata and other sources
Keywords: Rhetoric